2005
DOI: 10.1093/jee/98.2.577
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Evaluations of Transgenic Soybean Exhibiting High-Dose Expression of a Synthetic Bacillus thuringiensis cry1A Gene for Control of Lepidoptera

Abstract: Transgenic lines of soybean, Glycine max (L.) Merrill, expressing a synthetic cry1A gene (tic107) from Bacillus thuringiensis (Bt), were evaluated in screenhouse and conventional field trials for efficacy against lepidopteran pests. In screenhouse trials, Bt soybean and negative checks (isogenic segregants and parental lines) were evaluated against Anticarsia gemmatalis Hübner and Pseudoplusia includens (Walker) in the United States and against A. gemmatalis, Epinotia aporema (Walsingham), Rachiplusia nu (Guen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 33 publications
3
39
2
3
Order By: Relevance
“…The Cry1Ac protein is expressed in leaves, pollen/anthers, seeds, and pods, but not roots. The high-dose expression (25 times the amount required to kill 99% of a susceptible population) and concentration in the leaves can reach approximately 450 μg/g of the dry weight (MacRae et al 2005). …”
Section: Bt Soybeanmentioning
confidence: 99%
“…The Cry1Ac protein is expressed in leaves, pollen/anthers, seeds, and pods, but not roots. The high-dose expression (25 times the amount required to kill 99% of a susceptible population) and concentration in the leaves can reach approximately 450 μg/g of the dry weight (MacRae et al 2005). …”
Section: Bt Soybeanmentioning
confidence: 99%
“…It has been reported that a transgenic line of the soybean cultivar Jack expressing high levels of synthetic cry1Ac killed all A. gemmatalis larvae and significantly reduced the survival and feeding of the soybean looper (Pseudoplusia includens) and the corn earworm (Helicoverpa zea) in laboratory bioassays (Stewart et al, 1996) and in artificially infested field cages (Walker et al, 2000). More recently, Macrae et al (2005) evaluated transgenic soybean lines (based on cultivar A5547) expressing synthetic cry1A for resistance against several lepidopteran pests in screenhouse and conventional field trials carried out in the United States and Argentina and found that the Bt lines exhibited virtually complete efficacy against all the pests evaluated.…”
Section: Insecticidal Activitymentioning
confidence: 99%
“…The velvetbean caterpillar (Anticarsia gemmatalis Hübner) is a major soybean pest, mainly occurring in soybean growing regions of North and South America (Panizzi and Corrêa-Ferreira, 1997;Macrae et al, 2005), causes extremely high levels of defoliation when infestation is heavy and can severely damage axillary meristems, with a single caterpillar being able to consume up to 110 cm 2 of soybean foliage (Walker et al, 2000). However, various authors have reported that A. gemmatalis can be controlled by the delta-endotoxin (δ-endotoxin) produced by some strains of Bacillus thuringiensis (Stewart et al,1996;Walker et al, 2000;Macrae et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The search for resistant germplasms and investigation of their resistance mechanisms preceded such studies in Japan. Although transgenic crops are generally accepted in the United States, the effects of the transgene alone is not always sufficient for effective pest management 33,34,48 . Because these researchers believed that very high production of the Bt protein was needed to prevent the development of Bt-resistant insects, the native resistance of soybeans is also being used in breeding programs as a means of preventing the development of Bt resistance 51,52 .…”
Section: Introductionmentioning
confidence: 99%